A ray of hope for the hopeless: Hemisection of mandibular molar with socket preservation - Pushpendra K Verma; Ruchi Srivastava; Harak C Baranwal; Anju Gautam (Wolters Kluwer Medknow Publications, 2012)
Introduction: The management, treatment and long-term retention of mandibular molar teeth with furcation involvement have always been a challenge in periodontal therapy. Hemisection has been used successfully to retain teeth with furcation involvement. The term hemisection refers to the sectioning of a molar tooth, with the removal of an unrestorable root which may be affected by periodontal, endodontic, structural (cracked roots), or caries. Case Report : This case report describes a simple procedure of hemisection in a mandibular molar with socket preservation with help of an alloplastic bone graft and subsequent restoration of the tooth with fixed prothesis. Discussion: Hemisection represents a form of conservative procedure, which aims at retaining as much of the original tooth structure as possible. It may be a suitable alternative to extraction. Hemisection of the affected tooth allows the preservation of tooth structure, alveolar bone and cost savings (time and money) over other treatment options. The preservation of posterior abutment teeth permits oral rehabilitation with fixed bridges instead of removable prosthesis. Conclusion: The keys to long term success appear to be thorough diagnosis followed by interdisciplinary approach with endodontic, surgical and prosthetic procedures. Preservation of a hopeless tooth is possible by selecting patients with good oral hygiene, and careful surgical and restorative management.